FEATURES COUNTERCULTURE GROUPS FUNCTIONING IN THE INTERNET IN INFORMATION AGE - Мерщій, Т. В. (Proceedings of the Kyiv Aviation Institute. Series: Philosophy. Cultural, 2016)
This article examines transformation of countercultural groups of Internet communities by interests.